Different Fertilizers Applied Alter Fungal Community Structure in Rhizospheric Soil of Cassava (Manihot esculenta Crantz) and Increase Crop Yield - Cai, Jie; Zhang, Jie; Ding, Yun; Yu, Shan; Lin, Hongxin; Yuan, Zhanqi; Li, Kaimian; Ou, Wenjun; Chen, Songbi (Frontiers in Microbiology, 2021)
Soil microbes play an important role in the ecosystem, and have a relationship with plant growth, development and production. There are only a few reports on the effects of planting patterns of cassava on the microbial community structure in the rhizospheric soil. Here, we investigated the effects of different fertilization on the microbial community structure in cassava the rhizospheric soil. SC205 cultivar was used in this study as the experimental material. Compound fertilizer (CF) and reduced fertilizer (RF) were applied to the soil prior to planting. Soil samples were collected before harvest, and fungi were analyzed using IonS5TMXL sequencing platform. Results showed that CF and RF treatments significantly increased cassava yield. Amplicon sequencing result indicated that the fungi richness in rhizospheric soil of cassava was increased after CF applied, the diversity was decreased. However, the fungal diversity and richness were decreased in rhizospheric soil after RF applied. The most dominant fungal phylum was Ascomycota, which increased after fertilization. In addition, the abundance of beneficial fungi such as Chaetomium increased after fertilization, while that of pathogenic fungi such as Fusarium was decreased. The composition of the fungal community in rhizospheric soil with CF and RF applied was similar, but the richness and diversity of fungi were different. CCA analysis indicate there has a positive correlation between soil nutrition and fugal community structure. Overall, our results indicate that fertilization alters the fungal community structure of cassava rhizospheric soil, such that the abundance of beneficial fungi increased, while that of pathogenic fungi decreased, thereby significantly promoting plant growth and yield of cassava. Thus, during actual production, attention should be paid to maintain the stability of cassava rhizospheric soil micro-ecology.